PERANCANGAN MANAJEMEN ELECTRONIC FILING SYSTEM (E-FILING) DENGAN MENGGUNAKAN METODE ALFRED DI KANTOR DESA KUWARON, GROBOGAN - Ida Adha Kamilasari; Paulus Hartanto; Budi Hartono (STEKOM PRESS, 2019)
For this reason, the author makes the design of an electronic filing system (e-filing) management system, using the ALFRED method approach, namely: 1. Administrative Value (Value of use in administration), 2. Legal Value (Value of use in the field of law), 3. Fiscal Value (Use value in finance), 4.Research Value (Use value in the field of research), 5.Educational Value (Value use in education), 6.Documentative Value (Use value in the field of documentation). Making prototype application product Electronic Filing System (e-filing) management system uses Microsoft Visual Basic 6.0 software as a design media and as a programming language, and the SQL Server database as a storage media. This research was conducted using the Research & Development Method through a system design stage that was validated by experts and a prototype of a field-tested product involving users. The final result of this research is in the form of a prototype of an electronic filing system (e-filing) management system product that has been declared to function well so that it can produce information that is useful for the archiving process to the stage of making a report that can be done quickly and accurately in accordance with procedures that have been exist so as to make it easier to re-access archiving and provide public services with accurate and integrated information.